A Single Point Mutation Controls the Rate of Interconversion Between the g+ and g− Rotamers of the Histidine 189 χ2 Angle That Activates Bacterial Enzyme I for Catalysis - Purslow, Jeffrey A.; Thimmesch, Jolene N.; Sivo, Valeria; Nguyen, Trang T.; Khatiwada, Balabhadra; Dotas, Rochelle R.; Venditti, Vincenzo (Frontiers in Molecular Biosciences, 2021)
Enzyme I (EI) of the bacterial phosphotransferase system (PTS) is a master regulator of bacterial metabolism and a promising target for development of a new class of broad-spectrum antibiotics. The catalytic activity of EI is mediated by several intradomain, interdomain, and intersubunit conformational equilibria. Therefore, in addition to its relevance as a drug target, EI is also a good model for investigating the dynamics/function relationship in multidomain, oligomeric proteins. Here, we use solution NMR and protein design to investigate how the confrontational dynamics occurring within the N-terminal domain (EIN) affect the activity of EI. We show that the rotameric g+-to-g- transition of the active site residue His189 χ2 angle is decoupled from the state A-to-state B transition that describes a 90° rigid-body rearrangement of the EIN subdomains upon transition of the full-length enzyme to its catalytically competent closed form. In addition, we engineered EIN constructs with modulated conformational dynamics by hybridizing EIN from mesophilic and thermophilic species, and used these chimeras to assess the effect of increased or decreased active site flexibility on the enzymatic activity of EI. Our results indicate that the rate of the autophosphorylation reaction catalyzed by EI is independent from the kinetics of the g+-to-g- rotameric transition that exposes the phosphorylation site on EIN to the incoming phosphoryl group. In addition, our work provides an example of how engineering of hybrid mesophilic/thermophilic chimeras can assist investigations of the dynamics/function relationship in proteins, therefore opening new possibilities in biophysics.